The Hill Barbers - Inyang, Ekpe, 1963- (Book collections on Project MUSE., 2010)
Crafted in a colourful, razor-sharp blend of poetry and prose, The Hill Barbers depicts the wanton destruction of water catchments in most communities in Africa. This is inextricably linked to the traditional practice of shifting cultivation, motivated largely by farmers' struggle to acquire more arable farmland to meet the needs of their rapidly growing families. The immediate consequence is acute water shortages, with obvious health and economic implications. Agro-forestry and other soil management techniques are subtly proposed as practical measures to effectively address the issue of shifting cultivation and the associated problem of encroachment into the delicate water catchments.